An den Systemgrenzen: die zukünftige Rolle von LMS in hochschulischer (Tele-)Präsenzlehre - Christian Wolters (FernUniversität Hagen, 2021)
Learning management systems (LMS) take on a variety of tasks in the support of face-to-face higher education: from course organization to the distribution of learning media and provision of learning activities. Depending on the requirements of the educational institution, LMS cover these areas directly or integrate, at least interact, with external systems. On an individual level, further applications are used, for example from the areas of personal knowledge management, social media or communication systems. On an abstract level, all these applications form a network of applications, sometimes more and sometimes less well integrated, which are used in teaching and learning scenarios as needed. What role will the LMS play in the future in such a network of distributed applications, which is potentially expanding as a result of new developments? Will it remain the central hub of teaching and learning processes that it is today in many educational institutions, or will it disappear or merge into so-called Next Generation Digital Learning Environments (NGDLE) as decentralized applications become increasingly interconnected? This article discusses possible answers and consequences for the further development of LMS in the field of face-to-face teaching in higher education, taking into account the current societal conditions.